Implementasi Penegakan Sanksi Pidana Dalam Undang-Undang Nomor 44 Tahun 2008 Tentang Pornografi (Studi Kasus Di Wilayah Hukum Pengadilan Negeri Boyolali) - Arumawan, Dicky Putra, Muchammad Iksan, S.H. M.H (2016)
The Purposes of this research are to determine the penal law policy in Act Number 44 of 2008 regarding Pornography, the establishment of penal sanction of the Act Number 44 of 2008 regarding Pornography, and also the obstacles which is has experienced by the law enforcer to establish the penal sanction to criminal offender of pornography. The method used in this research is empirical juridical with descriptive study. The data source consists of primary data source, interviews and secondary data source, legal data primary, secondary and tertiary. Data collected from literature study and interviews then analyzed qualitatively. The results showed that Act Number 44 of 2008 regarding Pornography, contains flexible formulations regarding of criminal definition, it is very depends on perception, and it could inflict misinterpretations by the law enforcer in the field. The process of law enforcement regarding to pornography in Boyolali runs not very effective, the circulation of pornographies content are plenty in society, but from 2012 until 2016 only 1 (one) case which is handled by Polres Boyolali. Factors that obstructing the implementation of law enforcement of pornography penal law are Act factor, law enforcer factor, and society factor.